Functional Microbial Responses to Alcohol Abstinence in Patients With Alcohol Use Disorder - Gao, Bei; Emami, Atoosa; Zhou, Rongrong; Lang, Sonja; Duan, Yi; Wang, Yanhan; Jiang, Lu; Loomba, Rohit; Brenner, David A.; Stärkel, Peter; Schnabl, Bernd (Frontiers in Physiology, 2020)
Excessive alcohol consumption is associated with hepatic steatosis and dysregulation of the gut microbiota in patients with alcohol use disorder. However, how gut microbiota responds when patients stop drinking has not been well studied. In this study, we use shotgun metagenomic sequencing to elucidate the alterations in the functional capacity of gut microbiota in patients with alcohol use disorder when they stop drinking for two-weeks. Sensitive microbial pathways to alcohol abstinence were identified in alcohol use disorder patients. Further, we found the functional microbial responses to alcohol abstinence were different in alcohol use disorder patients with different degree of hepatic steatosis. Our results provide insights into the link between functional alterations of the gut microbiota and steatosis associated with alcohol consumption.